4a+(a+b)-(2a+3b) =4a +a+b-2a-3b=3a-2b
2(x+3y)-3(3x-y)=2x+6y-9x+3y=-7x+9y
2a+3-1,5a+0,5=0,5а+3,5 при a=-3,то 0,5*(-3)+3,5=-1,5+3,5=2
0,5а+3,5 при а=0,то 0,5*0+3,5=3,5
0,5а+3,5 ппри а=4,то 0,5*4+3,5=5,5
10-4(2x+5)=6y-13
4y-63=5(4x-2y)+2
4y-63-20x+10y-2=0
14y-65-20x=0
x=0.7y-3.25
3-8x-6y=0
3-8*(0.7y-3.25)-6y=0
3-5.6y+26-6y=0
29-11.6y=0
y=29/11.6y=2.пятых
14*2.5-65-20x=0
-30-20x=0
x=-30/20
x=-1.5
4a+(a+b)-(2a+3b) =4a +a+b-2a-3b=3a-2b
2(x+3y)-3(3x-y)=2x+6y-9x+3y=-7x+9y
2a+3-1,5a+0,5=0,5а+3,5 при a=-3,то 0,5*(-3)+3,5=-1,5+3,5=2
0,5а+3,5 при а=0,то 0,5*0+3,5=3,5
0,5а+3,5 ппри а=4,то 0,5*4+3,5=5,5